Design of a multilayer‐based collimated plane‐grating monochromator for tender X‐ray range. (20th December 2016) - Yang, Xiaowei; Wang, Hongchang; Hand, Matthew; Sawhney, Kawal; Kaulich, Burkhard; Kozhevnikov, Igor V.; Huang, Qiushi; Wang, Zhanshan
Abstract : A multilayer‐based collimated plane‐grating monochromator (cPGM) with efficiency one order of magnitude higher than the traditional cPGM is proposed for the tender X‐ray range. The resolving power can also be increased with improved photon flux by using a large blaze angle and working at high diffraction order. Abstract : Collimated plane‐grating monochromators (cPGMs), consisting of a plane mirror and plane diffraction grating, are essential optics in synchrotron radiation sources for their remarkable flexibility and good optical characteristics in the soft X‐ray region. However, the poor energy transport efficiency of a conventional cPGM (single‐layer‐coated) degrades the source intensity and leaves reduced flux at the sample, especially for the tender X‐ray range (1–4 keV) that covers a large number of K ‐ and L ‐edges of medium‐ Z elements, and M ‐edges of high‐ Z elements. To overcome this limitation, the use of a multilayer‐based cPGM is proposed, combining a multilayer‐coated plane mirror with blazed multilayer gratings. With this combination, the effective efficiency of cPGMs can be increased by an order of magnitude compared with the conventional single‐layer cPGMs. In addition, higher resolving power can be achieved with improved efficiency by increasing the blaze angle and working at higher diffraction order.